ADAPTING GLOBAL ESG PRINCIPLES TO REGIONAL TOURISM GOVERNANCE IN UZBEKISTAN (Marketing Jurnali, 2026)
This article examined the methodological foundations for developing integral indicators to assess socio-economic balance. International approaches to composite index construction, indicator selection, normalization, and aggregation were comparatively analyzed. The advantages of the Mazziotta-Pareto Index for evaluating balanced regional development were substantiated using established scientific sources. The findings demonstrated that the non-compensatory approach reflected regional socio-economic disparities more accurately and strengthened evidence-based decision-making in regional governance. The proposed methodology provided a comprehensive framework for assessing balanced territorial development and improving regional monitoring practices. The study concluded that the developed integral index could support more objective evaluation of regional performance and contribute to the improvement of socio-economic planning.